The industrialisation of Soviet Russia : 1. the socialist offensive : the collectivisation of Soviet agriculture - Davies, R.W. (London : Macmillan Press, 1989)
Bibliotheek François Vercammen
Engels
Meerdelige publicatie
Keywords: planeconomie; Sovjet-Unie.